REINTERPRETASI SURAH AL-MÃIDAH AYAT 51 DAN IMPLEMENTASINYA - Sulhadi, Asep (Jurnal al Hikmah, 2017)
This study discuss about the surah Al-Maidah verse 51. this became urgent because recently, in a few months this surah has been widely spoken by public. Commonly, they used it to ban Moslem electing non moslem leader. It did not stop to that case, most of Moslems supposed that we are prohibited to become their friend. As the result, the non moslem cooperations must be canceled, the products and the small bussines managed by non moslem must be banned. When this run for some periods, this would cause the relationship between moslems and non moslems less warmly, as the consideration that the basic prinsiple of Islamic teaching is to uphold the values of justice, tranquillity, humanity, equality,and morality. For the next period, this could change the islamic perspective which is well known by its friendly, hospitable, and full of tranquillity become disgracing. Furthermore, it would cause misperception and raise the negative perspective against islamic religion and moslem as a whole. This research used in this study was library research, while the research method was description method where the researcher wrote Al-Maidah and then referred to interpretation books to do research asbÃ¢b al-nuzÃ»l and the running interpratation by Ulama related to the verse above, it was then correlated to the factual life of Rasululloh SAW by referring to the hadith and concluded to this study. The result of this study was said by al-waliy as the homonym of one word which has many meanings. This word was taken from the roots of wauw, lam and yaâ and the basic meaning is close. This then created new meanings as like supporting, defender, protector, lover, frontier and ect, in which all of them was interconnected by a red thread, called closery.According to asbÃ¢b al-nuzÃ»l as the cause of this verse descended, it can be concluded that surah Al Maidah verse 51 prohibits us to have coalition, partnership, and have good friendship towards non Moslem if they do betrayal, disobidience, hostility openly, and fight againts us. The appearance of betrayal, disobidience, and the conspiracy become âilah (the cause) of the prohibition. When there is no âilah (the cause) as like non Moslem which acts fairly and tranquillity towards Moslem, so we have to respect and protect them as we respect and protect ourselves.